A Study of Support Characteristics of Collaborative Reinforce System of U-Steel Support and Anchored Cable for Roadway under High Dynamic Stress - Qizhou Wang; Haiwang Ye; Ning Li; Xiuwen Chi; Wenbing Xie; Dongfang Chen; Shengguo Jing; Tao Lei (Geofluids)
This paper presents a comprehensive study of the support effect and characteristics of a collaborative reinforce system of U-steel support and anchored cable (USS-AC) for roadway under high dynamic stress in a coal mine in China. The deformational behavior of the roadway and the load characteristics of reinforcing elements were measured in real time and analyzed. A numerical simulation study has also been conducted to identify the interaction of the reinforcing elements to the surrounding rock under dynamic load. The research results suggest that the stress distribution of roadway surrounding rock could be changed and that residual strength of the surrounding rock near opening could be increased by using USS-AC. Based on the action of anchored cable, the moment distribution of U-steel support is optimized. The load capacity and nondeformability of the U-steel support are promoted. And the global stability of U-steel support is enhanced so as to achieve the goal of high supporting resistance. When the deformation stress of the surrounding rock is higher, the U-steel support deforms as the surrounding rock. The two side beams and the overlapping parts of U-steel support suffer the highest deformation stress. As a result, the anchored cable provides higher reaction force for the previous locations of the U-steel support in order to prevent deformation of support towards to excavation. As an integral structure, the U-steel support is confined to a limited deformation space under the action of anchored cable. The larger deformation is released through sliding motion of the overlapping parts so as to reach the ultimate of high supporting resistance of USS-AC.